2013
DOI: 10.1016/j.jccase.2012.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Exercise-related QT interval shortening with a peaked T wave in a boy with MEN 2 syndrome

Abstract: Multiple endocrine neoplasia 2 (MEN 2) is a hereditary syndrome associated with medullary thyroid carcinoma, pheochromocytoma (PCC), and hyperparathyroidism. PCCs in patients with MEN 2 are usually found in the adrenals after the manifestation of medullary thyroid cancer and are commonly bilateral and hormonally active. Unfortunately, a diagnosis of MEN 2 or PCC often is delayed until after the patient has developed an advanced MEN 2-related tumor. We present unusual electrocardiographic changes on exercise te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…In this issue of Journal of Cardiology Cases , Gungor et al report the case of a MEN2 male patient with exercise-related QT interval shortening with a peaked T wave [17] . The resting ECG showed normal QTc interval of 394 ms.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In this issue of Journal of Cardiology Cases , Gungor et al report the case of a MEN2 male patient with exercise-related QT interval shortening with a peaked T wave [17] . The resting ECG showed normal QTc interval of 394 ms.…”
mentioning
confidence: 99%
“…Several studies reported that the effect of catecholamine is one of the secondary causes of short QT interval [13] , [19] , [20] . Gungor et al speculated that acute and massive catecholamine release caused a direct toxic effect on myocytes which resulted in these electrocardiographic changes [17] . The plasma catecholamine during exercise test in this patient was not measured but is thought to have increased, because a previous study reported that the post-exercise levels of epinephrine and the epinephrine/dopamine ratio were significantly higher in pheochromocytoma patients compared to healthy controls [21] .…”
mentioning
confidence: 99%